Towards a Society with Social Protection for All : A Concise History of Social Security Transformation in Modern China - Zhou, Hong; Zhang, Jun (Springer Singapore : Imprint: Springer, 2017)
This book systematically reviews the development of social policy since the establishment of the People's Republic of China. As such, it begins by investigating the establishment of the Insurance System in the early period, then moves on to the planned economy period, the Cultural Revolution period, and the Reform and Opening Up period, characterized by efforts to adapt to a market economy. For each period, the book examines the effect of the economic system, the mode of production and forms of employment for social policy design, so as to clarify the developing context of Chinese social policy, and to help readers grasp the legal aspects of social policy development and the main problems China faces in its present economic developmental stage.
Keywords: Social sciences.; Social policy.; Social service.; elektronické knihy; electronic books